Morphogenesis and forage yield of white oats (Avena sativa) under phosphorus sources and levels (Research, Society and Development, 2022)
The objective was to evaluate the morphology and forage yield of white oat cultivated under different doses and sources of phosphate fertilization. The experimental design used was completely randomized in a 4x2 factorial scheme, with five replications. The treatments were four doses of phosphorus: 0, 35, 70 and 140 kg ha-1 of P2O5, and two sources of phosphorus: simple superphosphate (18% of P2O5) and reactive natural phosphate (33% of P2O5). There was an effect (p